Lipid Metabolism, Abdominal Adiposity, and Cerebral Health in the Amish. Issue 11 (20th August 2017) - Ryan, Meghann; Kochunov, Peter; Rowland, Laura M.; Mitchell, Braxton D.; Wijtenburg, S. Andrea; Fieremans, Els; Veraart, Jelle; Novikov, Dmitry S.; Du, Xiaoming; Adhikari, Bhim; Fisseha, Feven; Bruce, Heather; et al.
Abstract : Objective: To assess the association between peripheral lipid/fat profiles and cerebral gray matter (GM) and white matter (WM) in healthy Old Order Amish (OOA). Methods: Blood lipids, abdominal adiposity, liver lipid contents, and cerebral microstructure were assessed in OOA ( N = 64, 31 males/33 females, ages 18‐77). Orthogonal factors were extracted from lipid and imaging adiposity measures. GM assessment used the Human Connectome Project protocol to measure whole‐brain average cortical thickness. Diffusion‐weighted imaging was used to derive WM fractional anisotropy and kurtosis anisotropy measurements. Results: Lipid/fat measures were captured by three orthogonal factors explaining 80% of the variance. Factor one loaded on cholesterol and/or low‐density lipoprotein cholesterol measurements; factor two loaded on triglyceride/liver measurements; and factor three loaded on abdominal fat measurements. A two‐stage regression including age/sex (first stage) and the three factors (second stage) examined the peripheral lipid/fat effects. Factors two and three significantly contributed to WM measures after Bonferroni corrections ( P < 0.007). No factor significantly contributed to GM. Blood pressure (BP) inclusion did not meaningfully alter the lipid/fat‐WM relationship. Conclusions: Peripheral lipid/fat indicators were significantly and negatively associated with cerebral WM rather than with GM, independent of age and BP level. Dissecting the fat/lipid components contributing to different brain imaging parameters may open a new understanding of the body‐brain connection through lipid metabolism.